2022
DOI: 10.1021/jacs.2c09146
|View full text |Cite
|
Sign up to set email alerts
|

Taming Keteniminium Reactivity by Steering Reaction Pathways: Computational Predictions and Experimental Validations

Abstract: Keteniminium ions, the nitrogen analogues of ketenes, exhibit high reactivity toward olefins and π-systems. Previous results from the Maulide group demonstrated an unexpected propensity for an alternative intramolecular Bellus− Claisen-type rearrangement rather than an expected intramolecular (2 + 2) cycloaddition. We have conducted a cooperative density functional theory/experimental investigation of this process, seeking insights into the competition between the observed Claisen-type reaction and the histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…We point out that during our preparation of this manuscript, Maulide and Houk reported their insightful mechanism of the [2 + 2] reaction of ene-keteniminium ions, which was found to be kinetically controlled for their substrates. 7,8 In our study reported here, the intramolecular [2 + 2] reactions of eneketeniminiums, with more examples compared to those in Maulide and Houk's paper, are very complex. We found that the regiochemistry 9 in some cases is kinetically controlled.…”
Section: ■ Introductionmentioning
confidence: 67%
“…We point out that during our preparation of this manuscript, Maulide and Houk reported their insightful mechanism of the [2 + 2] reaction of ene-keteniminium ions, which was found to be kinetically controlled for their substrates. 7,8 In our study reported here, the intramolecular [2 + 2] reactions of eneketeniminiums, with more examples compared to those in Maulide and Houk's paper, are very complex. We found that the regiochemistry 9 in some cases is kinetically controlled.…”
Section: ■ Introductionmentioning
confidence: 67%
“…In order to reveal the key role of the catalyst in the enantioselectivity control of the cascade Michael/cyclization reaction, we performed density functional theory (DFT) calculations at the M06-2X/6-311++G(d,p) (solvent = DCE, SMD)//M06-2X/6-31G(d,p) (vacuum) level to investigate the reaction pathway 12 (see ESI, Fig. S4 † ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, substituted cyclobutane motifs can be synthesized through two main methods in this condition. One is the addition of olefinic substrates to ketene [ 19 , 32 40 ] or keteniminium ions [ 41 49 ] to produce cyclobutanone, followed by multi-stage functional group transformations. This approach has been proven to be highly effective and reliable.…”
Section: [2 + 2] Cycloaddition Reactions Under Thermal Conditionsmentioning
confidence: 99%